Unveiling the Regional Identity of Madeira Wine: Insights from Saccharomyces cerevisiae Strains Using Interdelta Analysis - Mariangie M. Castillo; Nikol Parra; José S. Câmara; Mahnaz Khadem (Beverages, 2025)
The Demarcated Region of Madeira (DRM) is one of the oldest wine regions in Portugal, where the famous Madeira Wine (MW) is produced by spontaneous fermentation using endogenous yeasts. Several studies reported the role of endogenous Saccharomyces cerevisiae strains in the regional identity of wines, but only a few studies have been published in the DRM. The PCR-Interdelta (Polymerase Chain Reaction-Interdelta) analysis is a reliable method for S. cerevisiae strain identification. Here, we report the S. cerevisiae strains isolated from six Vitis vinifera grape varieties, namely, Tinta Negra, Boal, Sercial, Verdelho, Malvasia de São Jorge, and Complexa, which are widely used in MW production. During the 2020 campaign, eleven samples were collected from licensed vineyards and a winery, and submitted to spontaneous microfermentations and yeast isolation. Of the 1452 isolates counted, 1367 (94.2%) presented morphological characteristics of S. cerevisiae. We randomly selected 330 isolates from the positive colonies for strain identification. First, the PCR-Interdelta was optimized in ten commercial strains, using δ2–δ12 and δ12–δ21 pairs of primers, and δ2–δ12 primers were selected to screen the 330 isolates. We detected three fermentative profiles and a total of 25 PCR-Interdelta patterns were obtained, representing 7.6% of intraspecific variability, starting with the first non-official collection. The findings underscore the pivotal role of S. cerevisiae strain diversity in shaping the regional identity and quality of wines, with molecular tools like PCR-Interdelta analysis proving essential for monitoring intraspecific variability.